Kinerja Guru Bahasa Inggris Selama- Pasca Masa Pandemi - Kokok Dj Purwanto; Supeno Supeno (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2023)
Working as a teacher must be able to adjust, adapt oneself well to show strong performance as a professional teacher eventhough the situation and learning model have changed like in this pandemic period which previously were face to face directly turned into distance learning with an online system. This is a consideration of the various requirements that must be met by someone who wants to enter and serve himself in the world of education as a professional teacher. Therefore, whatever the changes, the situation and conditions, when the teacher works with dedicated professionals, it will produce students who are knowledgeable, having character and the best provisions in living life in the future.